Perceived service recovery justice and customer re-patronage intentions: Sequential mediation - Asghar Ali, M. (Cogent OA, 2021)
The aims of this time-lagged study are twofold, first to identify the effect of perceived justice (as a second-order construct) on recovery satisfaction and customer affection; secondly, to investigate the effect of customer affection and recovery satisfaction on customerâs re-patronage intentions. Data from 300 respondents (car insurance in Punjab, Pakistan) were analyzed using Structural Equation Modelling (PLS-SEM). The findings indicate that perceived service recovery justice (PSRJ) significantly predicts recovery satisfaction, customer affection and re-patronage intentions, and customer re-patronage intentions can be engendered through customer justice perception, positive appraisal of recovery satisfaction and customer affection. Recovery satisfaction and customer affection also indirectly explain the effect of PSRJ on re-patronage intentions (sequential mediation). Such findings have implications to theory and practice as it proposes and tested a new link between recovery satisfaction and customer affection. This research contributes to practice by providing strategies for effective service recovery and ultimately generates re-patronage intentions. Â© 2021 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.